(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article presents a scientific comparison of traditional and innovative technologies used in tomato drying. The effects of solar and convective drying methods, as well as vacuum, infrared, microwave, and freeze-drying technologies, on the quality, energy efficiency, and nutritional value of the final product are analyzed.